Effect of combined fatigue and chemical aging conditions on the mechanical property, structure, and morphology of styrene–butadiene–styrene elastomer. (December 2015) - Liu, Yuxin; Chen, Jian; Li, Guangxian; Liu, Xiaolin; Liao, Xia; Yang, Qi
The mechanical property, structure, and morphology of styrene–butadiene–styrene (SBS) thermoplastic elastomer under the combined fatigue and chemical aging conditions were investigated. The results indicated that under the fatigue condition alone, the tensile strength of SBS increased initially and then decreased with the increase in fatigue time. Cracks formed on the surface of samples. Through transmission electron microscopy analysis, it was found that the phase morphology was influenced by fatigue condition. However, there was no significant change in the molecular weight and chemical structure of SBS. Under combined fatigue and chemical aging conditions, the chemical aging process could be accelerated by the fatigue condition. Molecular weight and gel content significantly increased with the increase of fatigue condition. Under ultraviolet (UV) light irradiation alone, there was no crack on the surface of SBS. After adding the fatigue condition, a large deterioration formed on the surface of SBS sample. The chemical aging condition such as UV light and temperature could also promote the fatigue aging process. With the addition or increase of chemical aging condition, the tensile strength of SBS greatly decreased. The oxygen content and gel content significantly increased, and there were a lot of cracks forming on the surface of SBS sample.